2000
DOI: 10.2223/jped.73
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillation ventilation compared to conventional mechanical ventilation plus exogenous surfactant replacement in rabbits

Abstract: ResumoObjetivos: a) avaliar o efeito na oxigenação e ventilação de coelhos artificialmente depletados de surfactante quando submetidos à ventilação mecânica convencional associada à reposição parcial de surfactante exógeno; b) comparar a evolução deste grupo com outro grupo submetido à ventilação de alta freqüência por oscilação (HFO) sem reposição associada de surfactante.Métodos: Vinte coelhos brancos da raça New Zealand, peso de + 3 kg, foram anestesiados e artificialmente induzidos à depleção de surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Overdistension caused by increased airway pressure in CMV can be avoided when HFOV is used, preventing alveolar derecruitment and oscillations in alveolar volume (collapse and re-expansion), saving surfactant and decreasing local inflammation. 34 HFOV has shown consistent beneficial results in clinical and experimental ARDS. 11,15,24,35 In accordance with previous reports, our study confirmed that HFOV improved oxygenation, and reduced inflammatory and histopathological injuries.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Overdistension caused by increased airway pressure in CMV can be avoided when HFOV is used, preventing alveolar derecruitment and oscillations in alveolar volume (collapse and re-expansion), saving surfactant and decreasing local inflammation. 34 HFOV has shown consistent beneficial results in clinical and experimental ARDS. 11,15,24,35 In accordance with previous reports, our study confirmed that HFOV improved oxygenation, and reduced inflammatory and histopathological injuries.…”
Section: Discussionmentioning
confidence: 81%
“…17 Patients with ALI or ARDS ventilated at 6 mL/kg V T had a significant reduction in mortality compared with those ventilated at higher traditional V T . This concept leads to an interest in HFOV 24 as it uses a very small V T and constant 34 HFOV has shown consistent beneficial results in clinical and experimental ARDS. 11,15,24,35 In accordance with previous reports, our study confirmed that HFOV improved oxygenation, and reduced inflammatory and histopathological injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). We have previously observed that V T and ventilator frequency were closely related by measuring V T in animals ventilated at 5 and 15 Hz (26). Therefore, 5 Hz HFOV may have generated higher V T than 15 Hz HFOV, which, together with data from other experiments, suggests an inverse relationship between V T and ventilation frequency, whereby the former increases with decreasing ventilator fre- (4,27).…”
mentioning
confidence: 67%